Penerapan Metode Bernyanyi untuk Meningkatkan Hasil Belajar Mufradat Siswa DTA Baiturrohim Purwakarta - Lina, Lina; Munir, Dede Rizal (Kalimatuna: Journal of Arabic Research, 2023)
This research is motivated by the inefficiency of using vocabulary learning methods (mufradat) in Arabic language instruction. Many students perceive learning Arabic and memorizing mufradat as difficult and unenjoyable, leading to a decreased interest in learning the Arabic language. The research aims to investigate two aspects: 1) student learning activities in mufradat instruction using the singing method, and 2) student learning outcomes in mufradat instruction through the application of the singing method. The study was conducted at DTA Baeturrohim in Cibeber Village, Kiarapedes District, Purwakarta Regency. The research subjects comprised 16 students from grade 1 of DTA Baeturrohim in the academic year 2022/2023. This research employed a classroom action research design with qualitative and quantitative analysis methods. Data collection techniques included interviews, observations, tests, and documentation. The findings of this research can be summarized as follows: 1) The application of the singing method can enhance student learning activities, as evidenced by the increase in the percentage of student activities from 70% to 93%; 2) The application of the singing method can improve student learning outcomes in mastering mufradat, as demonstrated by increased learning achievement and the average learning outcomes of students in each action cycle.